Estudio de tiempos y movimientos en la elaboración de suelas para calzado en la empresa Preplast. - Llumitasig Tipantuña, Olger Germánico (2019)
The present research project aims to perform a study of times and movements in the injection molding process to increase the production levels of soles for footwear in the "PREPLAST" company; in that company there is no previous study to determine standard production times, unproductive times, cycle times, extra time to optimize the performance of the machinery. Performing an analysis of the current situation of the company through the study of times and movements that is an essential part of knowing the times of the activities during the injection molding process to standardize the procedures and reduce the time in which the operations are carried out to increase the productivity and competitiveness of the organization. Depending on the times, standards are established, which helps to have adequate planning and be able to project to the future efficiently and effectively. In the company, it is intended to increase production, through a study of times and movements in the process of the injection molding of soles for footwear. Finally, the company will increase productivity, labor efficiency, economic efficiency, production capacity, cost, and time reduction with the proposal. The work process is improved and the times in the manufacturing of soles are reduced, so that the product reaches the market in the shortest possible time to be competitive, and in this way saving time and money.